ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KESEJAHTERAAN PETANI (Studi Petani Bawang Merah di Desa Serading Kecamatan Moyo Hilir) - I Ismawati; Sarah Rizma Amalia (Pusat Riset dan Publikasi, 2021)
This study aims to analyze the effect of land area factors, production costs factor, selling price factors and production quantities factor toward the welfare of onion farmers in Serading Village, Moyo Hilir Sub-District. This study was causal associative research. The data collected was primary data obtained through questionnaires. The populations in this study were onion farmers in Serading Village with the number of population were 76. The technique used to determine sample was refer to Slovin formula. The numbers of sample were 53 samples. The data analysis techniques used were multiple linear regression analysis, t and F statistical tests and the determinant coefficient test (R2). The test was using the SPSS version 16.0 application for windows. The results of this study showed that the land area factor, production cost factor, selling price factor and production quantities factor had positive and significant effect toward the welfare of onion farmers either partially or simultaneously. The ability of the independent variables in affecting the welfare of onion farmers was 95% while the remaining of 5% was affected by other variables which were not examined.